2018
DOI: 10.1021/acs.est.8b03144
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Monitoring of Ligand Exchange Kinetics on Gold Nanoparticle Surfaces Enabled by Hot Spot-Normalized Surface-Enhanced Raman Scattering

Abstract: Nanoparticle surface coatings dictate their fate, transport, and bioavailability. We used a gold nanoparticle− bacterial cellulose substrate and "hot spot"-normalized surface-enhanced Raman scattering (HSNSERS) to achieve in situ and real-time monitoring of ligand exchange reactions on the gold surface. This approach enables semiquantitative determination of citrate surface coverage. Following exposure of the citrate-coated nanoparticles to a suite of guest ligands (thiolates, amines, carboxylates, inorganic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 62 publications
3
39
0
3
Order By: Relevance
“…Despite the slight difference in strength of the Au-Se and the Au-S bonds not all of the citrate was dislodged from the surface of the gold nanoparticles as the selenium SAM is formed, as suggested by the ATR-FTIR data. The evidence presented here indicates that citrate and other carboxylate-containing species residues are not easily displaced from the surface of gold nanoparticles, in accordance with previous studies [34][35][36].…”
Section: Characterization Of Capped-aunps By Uv-visible Spectroscopysupporting
confidence: 93%
See 2 more Smart Citations
“…Despite the slight difference in strength of the Au-Se and the Au-S bonds not all of the citrate was dislodged from the surface of the gold nanoparticles as the selenium SAM is formed, as suggested by the ATR-FTIR data. The evidence presented here indicates that citrate and other carboxylate-containing species residues are not easily displaced from the surface of gold nanoparticles, in accordance with previous studies [34][35][36].…”
Section: Characterization Of Capped-aunps By Uv-visible Spectroscopysupporting
confidence: 93%
“…These peaks could not be identified here, as a result of poor signal-to-noise measurements below 650 cm −1 (Figure S14). These bands could be better detected using Raman spectroscopy [36]. Alternatively, in order to provide evidence of the association of the AuNPs with SeCyst, TEM was used.…”
Section: Characterization Of Capped-aunps By Ftirmentioning
confidence: 99%
See 1 more Smart Citation
“…[96] Regarding one-step ligand exchange reactions, thiols replace carboxyls on gold due to higher adsorption energy, while amines with a similar energy were experimentally shown to overcoat rather than displace a citrate layer. [97] When using the binding energy as an indicator of the probability of bond formation, thiophene (T) derivatives, pyridine (Py), and thiols have a high probability to form bonds to metal surfaces compared to for example, amines. [98] The affinity of cyano (CN) ligands to gold is predicted to be high, yet in experiments CN has often been found to be a weak anchor group with low binding probability.…”
Section: Organic Surface Ligandsmentioning
confidence: 99%
“…Wei et al (2018) reported that the intensity of the surface plasmon enhanced elastic scattering signal (at 40 cm À1 in this case) scales linearly with the integrated "hot spot" signals within a laser excitation volume. Thus, intensity of other peaks can be quantified by using the peak intensity at 40 cm À1 as a normalizing factor (Wei et al 2019). In Figure 5a, colored box and whisker plots on the left show the median, average and 95 th , 75 th , 25 th , and 10 th percentile values and the right circles show the individual normalized intensity values.…”
Section: Detection Of Sers Signal From Laboratorygenerated Nanoparticlesmentioning
confidence: 99%